Identification of key proteins and pathways in cadmium tolerance of Lactobacillus plantarum strains by proteomic analysis - Qixiao Zhai (Nature Portfolio, 2017)
Abstract Our previous study confirmed the protective potential of Lactobacillus plantarum (L. plantarum) strains in alleviation of cadmium (Cd) toxicity in vivo and demonstrated that the observed protection largely depended on the tolerance of the strains to Cd-induced stress. It was also observed that there were significant intra-species differences in Cd tolerance of L. plantarum strains. In this study, we investigated the mechanism of Cd induced stress response of L. plantarum strains using the isobaric tags for relative and absolute quantitation (iTRAQ) based comparative proteomics. L. plantarum CCFM8610 (strongly resistant to Cd) and L. plantarum CCFM191 (sensitive to Cd) were selected as target strains, and their proteomic profiles in the presence and absence of Cd exposure were compared. We propose that the underlying mechanism of the exceptional Cd tolerance of CCFM8610 may be attributed to the following: (a) a specific energy-conservation survival mode; (b) mild induction of its cellular defense and repair system; (c) an enhanced biosynthesis of hydrophobic amino acids in response to Cd; (d) inherent superior Cd binding ability and effective cell wall biosynthesis ability; (e) a tight regulation on ion transport; (f) several key proteins, including prophage P2b protein 18, CadA, mntA and lp_3327.